2018
DOI: 10.1080/09205063.2018.1498184
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the research and application of biodegradable ureteral stents: from bench to bedside

Abstract: Ureteral stents are commonly used in urological practices but are frequently associated with patient discomfort, encrustation and stent-related infection. And a second procedure is needed to remove the stent. New biomaterials and designs have been attempted to solve these problems. The development of biodegradable ureteral stent shows promising prospects in future clinical applications. This article reviews the biomaterials and preparation methods commonly used in the present study of biodegradable ureteral st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…The most recent animal model studies have revealed a decrease in the appearance of obstructive fragments and adequate biocompatibility (6,7,25). However, BUS still show poor control of degradation rate, because their degradation in the animal model is too fast or because they feature a wide degradation time interval (6,7,25,26). BraidStent ® -H demonstrated a programmed and predictable degradation rate in this study; 91.7% of them completely degrade in the sixth week, for which it was designed.…”
Section: Treatment Of Us Focuses On Preservation Of Renal Functionmentioning
confidence: 69%
“…The most recent animal model studies have revealed a decrease in the appearance of obstructive fragments and adequate biocompatibility (6,7,25). However, BUS still show poor control of degradation rate, because their degradation in the animal model is too fast or because they feature a wide degradation time interval (6,7,25,26). BraidStent ® -H demonstrated a programmed and predictable degradation rate in this study; 91.7% of them completely degrade in the sixth week, for which it was designed.…”
Section: Treatment Of Us Focuses On Preservation Of Renal Functionmentioning
confidence: 69%
“…A crucial concern when producing a BUS is that the degradation profile of ureteral stents should occur in a controllable and adequate form, i.e. efficient mechanical properties must be assured during the treatment time and the degradation has to occur in an homogeneous way, avoiding additional ureteral obstruction [9,21,35]. In fact, these are very challenging features to obtain and constitute a critical point during the development process [3,35].…”
Section: Biodegradable Materialsmentioning
confidence: 99%
“…efficient mechanical properties must be assured during the treatment time and the degradation has to occur in an homogeneous way, avoiding additional ureteral obstruction [9,21,35]. In fact, these are very challenging features to obtain and constitute a critical point during the development process [3,35]. BUS have been fabricated from synthetic polymers, naturally origin polymers, biodegradable metals or a combination of biodegradable polymers and metals [3,35].…”
Section: Biodegradable Materialsmentioning
confidence: 99%
“…Various kinds of synthetic polymers have been used to prepare matrix and implant forms because of their distinctive advantages, such as excellent biocompatibility, controlled biodegradation rate, ideal mechanical strength, and hydrophobicity/hydrophilicity (Kim et al, 2014;Kapoor et al, 2015). Alpha hydroxy acids, such as polylactic acid (PLA), polyglycolic acid, poly (lactide-co-glycolide) (PLGA), polycaprolactone (PCL), polyethylene glycol, poly (lactide-cocaprolactone), polydioxanone, etc., were the most commonly used synthetic polymers (Wang L. et al, 2018). Moreover, it is noted that all these polymers were approved by the U.S. Food and Drug Administration (FDA) as biomaterials (Wang et al, 2015b) and Lumiaho et al (2007) fabricated a biodegradable ureteral stent by using PLA as the basic material.…”
Section: Synthetic Polymersmentioning
confidence: 99%